1992
DOI: 10.1148/radiology.182.2.1732943
|View full text |Cite
|
Sign up to set email alerts
|

Bronchogenic carcinoma: analysis of staging in the mediastinum with CT by correlative lymph node mapping and sampling.

Abstract: One hundred forty-three patients with bronchogenic carcinoma were studied prospectively with computed tomography (CT) to determine the accuracy of CT in the evaluation of mediastinal nodal metastases. Mediastinal lymph nodes were localized according to the lymph node mapping scheme of the American Thoracic Society and were considered abnormal if they exceeded 1 cm in short-axis diameter. All patients underwent surgical staging, which consisted of either mediastinoscopy alone or mediastinoscopy and thoracotomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
164
2
9

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(181 citation statements)
references
References 0 publications
6
164
2
9
Order By: Relevance
“…However, in 1992 MCLOUD et al [108] using a nodal short axis measurement of 1 cm in 143 patients, returned to less inspiring figures of 64% sensitivity and 62% specificity, respectively. These studies [105,106,108] all examined patients with presumed operable lung cancer in whom complete nodal sampling was performed either at mediastinoscopy or thoracotomy. Both LIBSHITZ and MCKENNA [105] and MCLOUD et al [108] observed an increase in false-positive nodes in patients with obstructive pneumonia.…”
Section: Nodal Statusmentioning
confidence: 97%
See 2 more Smart Citations
“…However, in 1992 MCLOUD et al [108] using a nodal short axis measurement of 1 cm in 143 patients, returned to less inspiring figures of 64% sensitivity and 62% specificity, respectively. These studies [105,106,108] all examined patients with presumed operable lung cancer in whom complete nodal sampling was performed either at mediastinoscopy or thoracotomy. Both LIBSHITZ and MCKENNA [105] and MCLOUD et al [108] observed an increase in false-positive nodes in patients with obstructive pneumonia.…”
Section: Nodal Statusmentioning
confidence: 97%
“…A meta-analysis in 1990 of 42 CT studies assessing mediastinal lymph node metastases from NSCLC described an overall sensitivity of 0.79, a specificity of 0.78 and an accuracy of 0.79 [107]. However, in 1992 MCLOUD et al [108] using a nodal short axis measurement of 1 cm in 143 patients, returned to less inspiring figures of 64% sensitivity and 62% specificity, respectively. These studies [105,106,108] all examined patients with presumed operable lung cancer in whom complete nodal sampling was performed either at mediastinoscopy or thoracotomy.…”
Section: Nodal Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported sensitiv ity of mediastinal lymph node staging by CT scan is ap proximately 60-80% [4, 9,13,19]. It is to be expected that modern CT scanning techniques, with the addition of intra venous contrast studies, will indicate whether a patient could benefit from a cervical mediastinoscopy or a para sternal procedure [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…CT is the most commonly used noninvasive staging method of the mediastinum, but is far from satisfying and less accurate than invasive surgical staging [51][52][53][54]. In prospective data from the Radiological Diagnostic Oncology Group, the sensitivity and specificity of thoracic CT were only 52% and 69% [55].…”
Section: Locoregional Lymph Node Stagingmentioning
confidence: 99%